ANALISIS PENGARUH PENANAMAN MODAL ASING (PMA), PENANAMAN MODAL DALAM NEGERI (PMDN) DAN EKSPOR TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI JAWA TIMUR TAHUN 2009-2019 - Avivi Makasmita Meliani; Sugeng Widodo; Ermatry Hariani (Jurnal Ilmu Ekonomi, 2021)
State development is a major development from a certain condition to a situation that is considered more valuable. One of the main requirements for economic growth is the investment criteria, apart from investment, of course, there are many factors that can affect economic growth, namely exports. The research objective to be achieved is to determine the effect of foreign investment, domestic investment, and exports on economic growth. The approach used in this research is quantitative. The variables of this study consist of independent variables, namely PMA, PMDN, and exports in East Java, while the dependent variable is economic growth. Data collection uses secondary data obtained from the Central Statistics Agency of East Java from 2009-2019. The data were analyzed using multiple linear regression analysis through the F test and T test with classical assumptions. The results of the study indicate that partially for PMA,PMDN,and exports have a significant effect on economic growth in East Java, and simultaneously there is a significant influence between PMA, PMDN, and exports on economic growth in East Java.